STRATEGI GURU DALAM MENGEMBANGKAN KECERDASAN INTERPERSONAL SISWA KELAS IV SEKOLAH DASAR - Wahyu Tri Laksono; Destrinelli; Hendra Budiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study is motivated by interpersonal intelligence which shows that students do not choose friends when going to study in groups, help mediate arguments between friends and be friendly to teachers. This study aims to describe the teacher's strategy in developing interpersonal intelligence of fourth grade students of SD Negeri III/IX Muhajirin. This study uses a qualitative approach, the purpose of this study is to describe the teacher's strategy in developing interpersonal intelligence of fourth grade students of SD Negeri III/IX Muhajirin. The results of this study obtained, the teacher's strategy carried out in developing interpersonal intelligence is as follows: (1) Teacher's Strategy as a Motivator in Developing Interpersonal Intelligence of Class IV Students of SDN 111 Muhajirin. As a motivator in developing students' interpersonal intelligence, teachers try to provide support to students so that they continue to be enthusiastic about learning and developing their potential. (2) Teacher's Strategy as an Educator in Developing Interpersonal Intelligence of Grade IV Students of SDN 111 Muhajirin. As an educator, the teacher delivers material using a variety of learning models and media. During learning, the teacher predominantly uses the teacher's verbal media (audio), in conveying material messages to students the teacher uses simple language and is easily understood by students.The teacher's delivery triggers two-way communication between teachers and students. (3) Teacher's Strategy as a Facilitator in Developing Interpersonal Intelligence of Grade IV Students of SDN 111 Muhajirin. The role of the teacher as a facilitator in developing students' interpersonal intelligence, namely by providing all the facilities needed by students. A teacher tries to provide all facilities for students in supporting teaching and learning activities carried out. If a student has difficulty in learning, a teacher is obliged to guide the student to be able to face and overcome the difficulties experienced.